1978
DOI: 10.1038/bjc.1978.167
|View full text |Cite
|
Sign up to set email alerts
|

Mammary-carcinoma cells in mouse liver: infiltration of liver tissue and interaction with Kupffer cells

Abstract: Summary.-Interactions between TA3 mammary-carcinoma cells and liver cells were studied with the electron microscope in mouse livers that had been perfused with a defined medium containing the tumour cells.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
39
0

Year Published

1986
1986
2011
2011

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 73 publications
(42 citation statements)
references
References 16 publications
3
39
0
Order By: Relevance
“…This is an in situ confirmation of previous in vitro findings concerning tumor cell binding prior to cytoxocity and phagocytosis. 14 -16 The presence of a single large DiO-filled phagosome in KCs indicates whole tumor cell phagocytosis and degradation in vivo, in concordance with the literature, 7,15,35,52 and parallel to the lysosomal localization of fluorescein in KCs 24 hr after injection of fluorescein-labeled colon cancer cells. 53 Lysosomal degradation of the ingested tumor cells was demonstrated by the subsequent appearance of smaller DiO-filled vacuoles resembling lysosomes at the electron microscopy level and the complete disappearance of the phagosome after 24 hr.…”
Section: Discussionsupporting
confidence: 74%
See 3 more Smart Citations
“…This is an in situ confirmation of previous in vitro findings concerning tumor cell binding prior to cytoxocity and phagocytosis. 14 -16 The presence of a single large DiO-filled phagosome in KCs indicates whole tumor cell phagocytosis and degradation in vivo, in concordance with the literature, 7,15,35,52 and parallel to the lysosomal localization of fluorescein in KCs 24 hr after injection of fluorescein-labeled colon cancer cells. 53 Lysosomal degradation of the ingested tumor cells was demonstrated by the subsequent appearance of smaller DiO-filled vacuoles resembling lysosomes at the electron microscopy level and the complete disappearance of the phagosome after 24 hr.…”
Section: Discussionsupporting
confidence: 74%
“…Others have reported only 40% similar contact for mammary carcinoma cells. 35 While the difference may be due in part to the different types of tumor cells used, our observation of a higher efficiency of contact may also be attributed to the use of intramesenteric injections, as opposed to liver perfusion, which may provide a more appropriate model for metastasis, and the more powerful CLSM to study KC-tumor cell interactions in 3 dimensions in large volumes.…”
Section: Discussionmentioning
confidence: 93%
See 2 more Smart Citations
“…Various studies have shown that interactions between these ECM components within the liver and tumor cells appear to be crucial to the formation of hepatic metastases (19)(20)(21). The liver is furthermore unique, since it lacks a basement membrane under the sinusoidal endothelium (22). This unique nature of the hepatic ECM is predicted by its special configuration and apparent continuity with the extraparenchymal areas of the connective tissue (23).…”
Section: Regulation By Circulation Patterns and Microvessels In Livermentioning
confidence: 99%